HUBUNGAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG KANKER PAYUDARA DENGAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI SMA NEGERI 12 PADANG - Elma Rezi (STIKes Al-Insyirah Pekanbaru, 2021)
Breast cancer is highest percentage of new cases of cancer (43.3%) and it is the second highest cause of death after lung cancer, namely 12.9%. This study aimed to determine The Correlation between Teenagers’ Level of Knowledge toward Breast Cancer with self-breast Examination at SMAN 12 Padang. The type of this research was analytic and cross sectional design. The samples were selected by proportional sample technique. Then, the data were analyzed by frequency distribution and Chi-square. The results of this research obtained that from 71 respondents, 37 students (52.1%) had low level of knowledge about breast cancer and 44 students (62.0%) did not do BSE was greater than who did breast self-examination. Next, based on the bivariate analysis, there was a significant correlation between the level of knowledge about breast cancer and breast self-examination with p = 0.013 (> 0.05). In short, it can be concluded that respondents who have a good level of knowledge about breast cancer will do breast self-examination as early detection in finding signs of breast cancer. However, the respondents who has a low level of knowledge about breast cancer will not do it.